GeroCast: Using podcasting to deliver living cases in gerontology education. (March 2023) - Auais, Mohammad; Cameron, Julie; Turnnidge, Jennifer; Dalgarno, Nancy; Kolomitro, Klodiana; Pelland, Lucie
Objective: To describe the creation of an educational podcast with 'living cases' of older adults to support students' learning on a gerontology course and report on students' evaluation of the project. Setting: Gerontology course in a graduate programme. Method: We developed a podcast series based on interviews with older adults in the community following recent guidelines for creating educational podcasts. The podcast episodes were used in a case-based group assignment to work on during the course and to present findings at the end. Evaluation: Student experiences were evaluated using a mixed-methods survey. Results: From November 2019 to January 2021, case-based podcasts, averaging 17 minutes in length, were created and evaluated. Most students found the content of the podcasts relevant to working with older adults and increased their understanding of the issues facing members of that population. Qualitative analysis of the survey findings found that the overall strengths of the podcasts were that they were well structured, provided an authentic, real-world experience, allowed listeners to experience an innovative teaching strategy, promoted reflection, and encouraged students to consider a future career working with older adults. Students also recommended ways to improve the podcasts. Conclusion: Delivering living case studies using podcasts is a feasible, inexpensive and effective teaching method for improving physiotherapy students' attitudes towards caring for older adults. Students enjoyed learning via the podcasts and found them a valuable way to better understand the issues facing older adults. The living case podcasts could have broad applicability to other aging and health courses.